Catalytic Amyloids as Novel Synthetic Hydrolases - Diaz-Espinoza, R (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Amyloids are supramolecular assemblies composed of polypeptides stabilized by an in-termolecular beta-sheet core. These misfolded conformations have been traditionally associated with pathological conditions such as Alzheimer’s and Parkinson´s diseases. However, this classical paradigm has changed in the last decade since the discovery that the amyloid state represents a universal alternative fold accessible to virtually any polypeptide chain. Moreover, recent findings have demonstrated that the amyloid fold can serve as catalytic scaffolds, creating new opportunities for the design of novel active bionanomaterials. Here, we review the latest advances in this area, with particular emphasis on the design and development of catalytic amyloids that exhibit hydrolytic activities. To date, three different types of activities have been demonstrated: esterase, phospho-esterase and di-phosphohydrolase. These artificial hydrolases emerge upon the self-assembly of small peptides into amyloids, giving rise to catalytically active surfaces. The highly stable nature of the amyloid fold can provide an attractive alternative for the design of future synthetic hydrolases with diverse applications in the industry, such as the in situ decontamination of xenobiotics. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.